Decreased neuron loss and memory dysfunction in pilocarpine-treated rats pre-exposed to hypoxia. (22nd September 2016) - Do Val-da Silva, Raquel Araujo; Peixoto-Santos, José Eduardo; Scandiuzzi, Renata Caldo; Balista, Priscila Alves; Bassi, Mirian; Glass, Mogens Lesner; Romcy-Pereira, Rodrigo Neves; Galvis-Alonso, Orfa Yineth; Leite, João Pereira
Highlights: Hypoxic preconditioning increased latency to pilocarpine-induced status epilepticus. Preconditioned rats had better memory performance than non-preconditioned group. Neuropathological changes were milder in preconditioned animals submitted to status. Abstract: Preconditioning can induce a cascade of cellular events leading to neuroprotection against subsequent brain insults. In this study, we investigated the chronic effects of hypoxic preconditioning on spontaneous recurrent seizures (SRS), neuronal death, and spatial memory performance in rats subjected to pilocarpine (Pilo)-induced status epilepticus (SE). Rats underwent a short hypoxic episode (7% O2  + 93% N2 ; 30 min on two consecutive days) preceding a 4-h SE (HSE group). Control groups were rats submitted to SE only (SE), rats subjected to hypoxia only (H) or normoxia-saline (C). Animals were monitored for the occurrence of SRS, and spatial memory performance was evaluated in the radial-arm maze. Hippocampal sections were analyzed for cell death and mossy fiber sprouting at 1 or 60 days after SE. Compared to SE group, HSE had increased SE latency, reduced number of rats with SRS, reduced mossy fiber sprouting at 60 days, and reduced cell death in the hilus and the CA3 region 1 and 60 days after SE. Additionally, HSE rats had better spatial memory performance than SE rats. Our findings indicated that short hypoxic preconditioning preceding SE promotes long-lasting protective effects on neuron survival and spatial memory.